ANALISIS GAMBARAN DAN IMPLEMENTASI “ANDINGINGI” SEBAGAI RITUAL ADAT SUKU KAJANG DI TANA TOA: KAJIAN ETNOGRAFI - Tajirah Umajjah; Ikhwan M. Said; Asriani Abbas (Bajang Institute, 2021)
This type of research used in this research is descriptive qualitative, the process of collecting data intensively and systematically in order to obtain information and knowledge. So, in this study the researchers observed and interacted with the people in Tana Toa Village, Kajang Subdistrict, Bulukumba Regency by interviewing and reviewing the documentation. This study aims to determine the description of the Andingingi tradition and the implementation of Andingingi social values ​​in the community of Tana Toa Village, Kajang District, Bulukumba Regency. Based on the results of the study, it can be seen that the description of the Andingingi tradition in Tana Toa Village, Kajang District, Bulukumba Regency is actually a kind of earth and life ritual, where prayers are prayed so that within the next year, safety and health will always be given from Tu Rie ' Ara'na or Almighty God. Implementation of social values ​​contained in the Andingingi tradition in social life such as mutual cooperation, please help, solidarity and communicative. It is expected that there will be special attention from the government and the Kajang community not to be taboo with progress and modernization, but with all the abilities to maintain the existence of traditions, one of which is the andinging culture.